Penerapan Metode Pembelajjaran Inquiry Dalam Meningkatkan Hasil Belajar Bahasa Indonesia - S, Yusniar (JURNAL GLOBAL EDUKASI, 2020)
Abstract: Classroom action research in general aims to improve student learning outcomes by applying the Inquiry learning method in Indonesian language lessons with the theme of the events of class III SDN 010009 Kapias Batu VIII kec. Tanjung Balai TP. 2018/2019. The subjects of this study were third grade students of SDN 010009 Kapias Batu VIII. Data were collected through observation, interviews, tests, and documentation study. The results of the learning process before research through the Inquiry learning method reached an average value of 64.81, after being motivated, the research was carried out through the first cycle and the second cycle of reflection and the recommended average value reached 89.13, meaning there was an increase of 24.32. Classical mastery learning outcomes in the first cycle reached an average value of 77.13% after cycle I and cycle II, reflection and learning completeness reached 89.13%, which means there was an increase of 12%. Keywords: inquiry; event  Abstrak: Penelitian tindakan kelas secara umum bertujuan untuk meningkatkan hasil  belajar siswa dengan menerapan metode pembelajaran Inquiry pada pelajaran Bahasa Indonesia dengan tema Peristiwa siswa kelas III SDN 010009 Kapias Batu VIII  kec. Tanjung Balai TP. 2018/2019. Subjek penelitian ini adalah siswa kelas III SDN 010009 Kapias Batu VIII, data dikumpulkan melalui observasi, wawancara, test, dan studi dokumentasi. Hasil proses belajar sebelum penelitian melalui metode pembelajaran Inquiry mencapai nilai rata-rata 64.81, setelah termotivasi dilakukan penelitian melalui siklus I dan siklus II refleksi dan rekomendasi nilai rata-rata mencapai 89.13 berarti ada peningkatan sebesar 24.32. Ketuntasan klasikal hasil belajar pada siklus I mencapai nilai rata-rata 77.13% setelah siklus I dan siklus II, refleksi dan reko-mendasi ketuntasan belajar mencapai 89.13% berarti ada peningkatan sebesar 12%.            Kata Kunci: inquiry; peristiwa